Fluid inertia force effects in hydromagnetic sphere-plate squeeze films. (January 2015) - Lin, Jaw-Ren
Abstract: This paper investigates the influences of fluid inertia forces in hydromagnetic sphere-plate squeeze films. Applying the averaged inertia principle, a megnetohydrodynamic pressure gradient equation has been derived. From the results obtained, the combined effects of fluid inertia forces and electrical conducting fluids in the presence of external magnetic fields provide better squeeze film characteristics, and lengthen the operating life of the sphere-plate system as compared to the non-inertia non-conducting-fluid case. Highlights: Fluid inertia effects in hydromagnetic sphere-plate squeeze films are investigated. A magnetohydrodynamic pressure gradient equation is derived using the averaged inertia principle. Fluid inertia forces improve the squeeze film performance of hydromagnetic sphere-plate system.